Solar Eruptions in Nested Magnetic Flux Systems - Judith T. Karpen; Pankaj Kumar; Peter F. Wyper; C. Richard DeVore; Spiro K. Antiochos (The Astrophysical Journal, 2024)
The magnetic topology of erupting regions on the Sun is a key factor in the energy buildup and release, and the subsequent evolution of flares and coronal mass ejections (CMEs). The presence/absence of null points and separatrices dictates whether and where current sheets form and magnetic reconnection occurs. Numerical simulations show that energy buildup and release via reconnection in the simplest configuration with a null, the embedded bipole, is a universal mechanism for solar eruptions. Here we demonstrate that a magnetic topology with nested bipoles and two nulls can account for more complex dynamics, such as failed eruptions and CME–jet interactions. We investigate the stalled eruption of a nested configuration on 2013 July 13 in NOAA Active Region 11791, in which a small bipole is embedded within a large transequatorial pseudo-streamer containing a null. In the studied event, the inner active region erupted, ejecting a small flux rope behind a shock accompanied by a flare; the flux rope then reconnected with pseudo-streamer flux and, rather than escaping intact, mainly distorted the pseudo-streamer null into a current sheet. EUV and coronagraph images revealed a weak shock and a faint collimated outflow from the pseudo-streamer. We analyzed Solar Dynamics Observatory and Solar TErrestrial RElations Observatory observations and compared the inferred magnetic evolution and dynamics with three-dimensional magnetohydrodynamics simulations of a simplified representation of this nested fan-spine system. The results suggest that the difference between breakout reconnection at the inner null and at the outer null naturally accounts for the observed weak jet and stalled ejection. We discuss the general implications of our results for failed eruptions.